Racial Diversity in U.S. Congregations, 1998–2019 - Dougherty, Kevin D. (Journal for the scientific study of religion, 2020)
Racially diverse congregations have become an important part of the American religious landscape. We use data from the National Congregations Study (NCS), notably including data from the fourth wave, collected in 2018-2019, to examine 20 years of racial diversity in congregations. We find that racial diversity within congregations has increased substantially between 1998 and 2019. There are more congregations in which no one racial or ethnic group comprises more than 80 percent of the people, congregations’ average diversity level has increased, and the percentage of all-white congregations has declined. Nearly a quarter of evangelical churches now have no one ethnic group constituting more than 80 percent of the people, a rate comparable to what we observe among Catholic churches. Moreover, congregations that meet this 80-percent threshold are more likely to be led by black clergy in 2019 than they were in 1998. We end with a note of caution about concluding that diverse congregations necessarily promote racial justice.